Mass spectrometry insights into a tandem ubiquitin‐binding domain hybrid engineered for the selective recognition of unanchored polyubiquitin. Issue 14 (21st July 2016) - Scott, Daniel; Garner, Tom P; Long, Jed; Strachan, Jo; Mistry, Sharad C.; Bottrill, Andrew R.; Tooth, David J.; Searle, Mark S.; Oldham, Neil J.; Layfield, Rob
Abstract : Unanchored polyubiquitin chains are emerging as important regulators of cellular physiology with diverse roles paralleling those of substrate‐conjugated polyubiquitin. However tools able to discriminate unanchored polyubiquitin chains of different isopeptide linkages have not been reported. We describe the design of a linker‐optimized ubiquitin‐binding domain hybrid (t‐UBD) containing two UBDs, a ZnF‐UBP domain in tandem with a linkage‐selective UBA domain, which exploits avidity effects to afford selective recognition of unanchored Lys48‐linked polyubiquitin chains. Utilizing native MS to quantitatively probe binding affinities we confirm cooperative binding of the UBDs within the synthetic protein, and desired binding specificity for Lys48‐linked ubiquitin dimers. Furthermore, MS/MS analyses indicate that the t‐UBD, when applied as an affinity enrichment reagent, can be used to favor the purification of endogenous unanchored Lys48‐linked polyubiquitin chains from mammalian cell extracts. Our study indicates that strategies for the rational design and engineering of polyubiquitin chain‐selective binding in nonbiological polymers are possible, paving the way for the generation of reagents to probe unanchored polyubiquitin chains of different linkages and more broadly the 'ubiquitome'. All MS data have been deposited in the ProteomeXchange with identifier PXD004059 (http://proteomecentral.proteomexchange.org/dataset/PXD004059 ).